Pola Implementasi Pelatihan Batik Cap Interaktif Motif Khas Pacitan untuk Anak Usia Sekolah Dasar - Ratnawati, Ike; Prasetyo, Abdul Rahman; Iriaji, Iriaji; Wardhana, Mitra Istiar; Aruna, Alby; Surya, Eka Putri; Marcelliantika, Adinda (VISA: Journal of Vision and Ideas, 2024)
The implementation pattern of interactive stamp batik training with typical motifs of Pacitan Regency for elementary school children is designed based on adaptive learning and digital technopreneurship. The purpose of this training is to introduce batik skills from an early age and equip children with technological and entrepreneurial skills. Using a qualitative descriptive approach, data was collected through observation, interviews, and document analysis. The results showed a significant increase in children’s understanding and skills in making batik stamps, as well as a greater appreciation of local cultural heritage. Training also contributes to the development of technology-based entrepreneurial skills. Challenges related to limited access to technology and training materials have been successfully overcome with an adaptive and collaborative approach.